Trends in cord blood banking - Arrojo, Isidro Prat (Edizioni SIMTI — SIMTI Servizi Srl, 2012)
BACKGROUND: Umbilical cord blood (UCB) is a source of hematopoietic precursor cells for transplantation. The creation of UCB banks in 1992 led to the possibility of storing units of UCB for unrelated transplants. The distribution of cell contents in historical inventories is not homogenous and many units are not, therefore, suitable for adults. The aim of this study was to analyse our UCB bank inventory, evaluate the units released for transplantation and calculate the cost of the current process per unit of UCB stored. METHODS: Three study periods were defined. In the first period, from January 1996 to January 2006, the total nucleated cell (TNC) count acceptable for processing was 4–6×10(8) and a manual processing system was used. In the second period, from October 2006 to July 2010, processing was automated and the acceptable TNC count varied from 8–10×10(8). In the third period, from January 2009 to June 2010, an automated Sepax-BioArchive procedure was used and the accepted initial TNC count was >10×10(8). Within each period the units were categorised according to various ranges of cryopreserved TNC counts in the units: A, >16.2×10(8); B1, from 12.5–16.1×10(8); B2, from 5.2–12.4×10(8); and C, <5.1×10(8). RESULTS: The third period is best representative of current practices, with homogenous TNC acceptance criteria and automated processing. In this period 15.7% of the units were category A and 25.5% were category B. Overall, the mean TNC count of units released for transplantation was 14×10(8) (range, 4.6×10(8) to 36.5×10(8)). The cost of the processed UCB in 2009 was 720.41 euros per unit. CONCLUSION: An UCB bank should store units of high-quality, in terms of the TNC count of units issued for transplantation, have a training programme to optimise the selection of donors prior to delivery, use similar volume reduction systems and homogenous recovery indices, express its indicators in the same units, use validated analytical techniques, and bear in mind ethnic minorities.